2006
DOI: 10.1128/jvi.80.9.4482-4490.2006
|View full text |Cite
|
Sign up to set email alerts
|

Junctional Adhesion Molecule 1 Is a Functional Receptor for Feline Calicivirus

Abstract: The life cycle of calicivirus is not fully understood because most of the viruses cannot be propagated in tissue culture cells. We studied the mechanism of calicivirus entry into cells using feline calicivirus (FCV) The family Caliciviridae comprises a diversity of pathogens in humans and animals. Studies of the life cycle of the virus have been quite limited because of the lack of cell culture methods for most caliciviruses (13). Porcine enteric calicivirus in the genus Sapovirus is known to propagate in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
136
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 32 publications
1
136
0
1
Order By: Relevance
“…A big break through for FCV research was recently reported when the junctional adhesion molecule-1 (JAM-1) was identified as a cellular receptor for FCV in cell culture [62]. Transfection of nonpermissive cells with a JAM-1 expression system rendered the cell line permissive for FCV and anti-feline JAM-1 antibodies reduced replication of FCV in permissive cells.…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…A big break through for FCV research was recently reported when the junctional adhesion molecule-1 (JAM-1) was identified as a cellular receptor for FCV in cell culture [62]. Transfection of nonpermissive cells with a JAM-1 expression system rendered the cell line permissive for FCV and anti-feline JAM-1 antibodies reduced replication of FCV in permissive cells.…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…Ossiboff and Parker have identified three amino acid residues, mutation of which led to reductions in binding to FCV strain 5: D42, K43, and S97 (18). In their initial study describing fJAM-A as the functional receptor for FCV, Makino et al (15) proposed that S91 and K155 may also be important, following comparison of sequences for fJAM-A and simian JAM-A (which bind FCV) with human JAM-A (which does not). Of these residues, only K155 is not close to or part of the footprint we have identified through our fitting experiments (Fig.…”
Section: Figmentioning
confidence: 99%
“…FCV is arguably the best characterized of these and to date is the only calicivirus for which a protein receptor has been identified. FCV binds to ␣-2,6-sialic acid and to feline junctional adhesion molecule A (fJAM-A, also known as fJAM-1) (15,25). Transfection of fJAM-A into nonpermissive cells renders them susceptible to FCV infection, while antibodies directed against fJAM-A can be used to inhibit FCV entry.…”
mentioning
confidence: 99%
“…Recent findings of FCV and MNV binding to sialic acid (Rydell et al, 2009;Stuart & Brown, 2007;Taube et al, 2009) or heparan sulfate (Tamura et al, 2004) broadens the spectrum of sugar residues that interact with these viruses. Moreover, the identification of a membrane protein, the junctional adhesion molecule A (JAM-A), as a receptor for FCV (Makino et al, 2006) raises the hypothesis of this protein or other members of the Ig superfamily being also cellular receptors for caliciviruses, like they are for reoviruses and picornaviruses (Tan & Jiang, 2010). According to the proposed model for reoviruses, the virus interact firstly with a sugar residue like sialic acid, as a determinant of tropism that is responsible for initial virus attachment, and later use a membrane protein (JAM-1) to enter the host cell (Barton et al, 2001).…”
Section: Targeting Cellular Receptors Of Norovirusmentioning
confidence: 99%